Integrated access to information utilities: Promises, problems and profiles of the future/ L’accès intégré aux sources d’information: Promesses, problèmes et profil de l’avenir - Meadow, Charles T. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
See PDF